Exploring the EFL learners' attitudes towards the integration of active reading software in learning reading comprehension at tertiary level - Khan, Imran; Ainol Haryati, Ibrahim; Asiah, Kassim; Khan, Raja Muhammad Ishtiaq (Model Institute of Education & Research, 2020)
The role of technology in language pedagogy and learning is significant both in EFL and ESL contexts. Educational technology facilitates language teachers to enhance their teaching practices by implementing certain strategies to assist learners to achieve their academic goals successfully. However, the adoption and effective use of technology in EFL classes depend on the positive attitudes of the learners. The current study attempts to explore EFL learners' attitude towards technology-enhanced instructions of reading comprehension at Majmaah University, Saudi Arabia. Participants of the study consisted of 60 male EFL learners, divided into two pre-formed groups. The study adopted a quantitative approach, and an attitude scale questionnaire was administered to explore the learners' attitude towards Active Reading Software (ARS) instruction. The experimental group received four-week treatment in the computer labs using ARS. The results of the descriptive statistics indicated positive attitudes of EFL learners toward Active Reading Software as a learning tool in improving reading comprehension achievement.